World history: great civilizations - Heggie, Jon (National Geographic Learning, Cengage Learning, 2016)
Unit 1. Origins of cultures and civilizations (175,000 B.C.-3000 B.C.) -- Chapter 1. The development of human societies -- Chapter 2. Origins of civilization -- Unit 2. Early civilizations (3000 B.C.-A.D. 535) -- Chapter 3. Ancient Mesopotamia -- Chapter 4. Ancient Egypt -- Chapter 5. Judaism and the Israelite kingdoms -- Chapter 6. Ancient India -- Chapter 7. Ancient China -- Unit 3. Greek civilization (2000 B.C.-323 B.C.) -- Chapter 8. Ancient Greece -- Chapter 9. Classical Greece -- Unit 4. The world of the Romans (509 B.C.-A.D. 476) -- Chapter 10. The Roman Republic -- Chapter 11. The Roman Empire and Christianity -- Unit 5. Byzantine and Islamic civilizations (330-1858) -- Chapter 12. The Byzantine Empire -- Chapter 13. The Islamic world -- Unit 6. African civilizations (1000 B.C.-A.D. 1500) -- Chapter 14. North and West Africa -- Chapter 15. East, Central, and Southern Africa -- Unit 7. American civilizations (1200 B.C.-A.D. 1600) -- Chapter 16. Mesoamerica -- Chapter 17. South and North America -- Unit 8. Empires of Asia (400-1912) -- Chapter 18. Dynasties of China -- Chapter 19. Japanese civilization -- Chapter 20. Korea and Southeast Asia -- Unit 9. Medieval and Renaissance Europe (500-1700) -- Chapter 21. Feudalism and the Middle Ages -- Chapter 22. Renaissance and Reformation -- Chapter 23. The age of science and exploration -- Unit 10. Revolutions and empires (1600-1914) -- Chapter 24. Enlightenment and revolution -- Chapter 25. Factories, nations, and empires -- Unit 11. The modern world (1900-Present) -- Chapter 26. The world at war -- Chapter 27. Global connections